Evidence for Sprouting of Dopamine and Serotonin Axons in the Pallidum of Parkinsonian Monkeys - Gagnon, Dave; Eid, Lara; Coudé, Dymka; Whissel, Carl; Di Paolo, Thérèse; Parent, André; Parent, Martin (Frontiers in Neuroanatomy, 2018)
This light and electron microscopic immunohistochemical quantitative study aimed at determining the state of the dopamine (DA) and serotonin (5-HT) innervations of the internal (GPi) and external (GPe) segments of the pallidum in cynomolgus monkeys (Macaca fascicularis) rendered parkinsonian by systemic injections of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). In contrast to the prominent DA denervation of striatum, the GPi in MPTP monkeys was found to be markedly enriched in DA (TH+) axon varicosities. The posterior sensorimotor region of this major output structure of the basal ganglia was about 8 times more intensely innervated in MPTP monkeys (0.71 ± 0.08 x 106 TH+ axon varicosities/mm3) than in controls (0.09 ± 0.01 × 106). MPTP intoxication also induced a two-fold increase in the density of 5-HT (SERT+) axon varicosities in both GPe and GPi. This augmentation was particularly pronounced anteriorly in the so-called associative and limbic pallidal territories. The total length of the labeled pallidal axons was also significantly increased in MPTP monkeys compared to controls, but the number of DA and 5-HT axon varicosities per axon length unit remained the same in the two groups, indicating that the DA and 5-HT pallidal hyperinnervations seen in MPTP monkeys result from axon sprouting rather than from the appearance of newly formed axon varicosities on non-growing axons. At the ultrastructural level, pallidal TH+ and SERT+ axons were morphologically similar in MPTP and controls, and their synaptic incidence was very low suggesting a volumic mode of transmission. Altogether, our data reveal a significant sprouting of DA and 5-HT pallidal afferents in parkinsonian monkeys, the functional significance of which remains to be determined. We suggest that the marked DA hyperinnervation of the GPi represents a neuroadaptive change designed to normalize pallidal firing patterns associated with the delayed appearance of motor symptoms, whereas the 5-HT hyperinnervation might be involved in the early expression of non-motor symptoms in Parkinson's disease.